CONSUMPTIVE IDEOLOGY HEGEMONY AS A LIFESTYLE IN RANS ENTERTAIMENT YOUTUBE CONTENT: GRAMSCI'S HEGEMONY STUDY - Agustina Purwanti; Maman Suryaman (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
The current of significant changes in lifestyle has developed through the development of technological flows in social media. Social media has a strong influence in shaping knowledge and character, both from the upper-, middle-, and lower-class groups. Content packaging is represented as natural as possible in instilling its influence so that hegemony practices occur. Contents that emphasize and highlight consumptive culture are used as a mainstay to attract the attention of viewers through the Youtube channel to increase the number of viewers and earn profits. This practice is what makes consumptive hegemony approval. This study describes how the process of hegemony in forming a consumptive ideology uses a qualitative study with a literature approach to strengthen the explanation of Gramsci's hegemony. The object of the analysis of the Youtube Rans Entertainment channel that was taken was the content entitled “Wow!!! Raffi Nagita opens a nightly hangout in front of the house…” and “Nagita Try Online Items for Under 100K!!! The result makes you laugh!!!". Both contents are packaged in a relaxed atmosphere full of joy by fostering a fun effect in emphasizing consumptive ideology. Social media provides closeness between the audience and content owners so that the practice of hegemony is easily approved. In defending the consumptive ideology, the dominant group makes representations that allow for a good response. This hegemony makes the consumptive ideology develop into a lifestyle.